Study of psychiatric disorders among nepalese patients working abroad and their family members - Yengkokpam, B; Shah, SK; Bhantana, GR (Journal of College of Medical Sciences-Nepal, 2012)
This study was carried out among the patients working abroad and their family members, having various psychiatric disorders. 80 patients attending psychiatry OPD between the age of 15 to 65 years both male and female in the period of July 2009 to July 2010 were included. The results were tabulated as per the diagnostic criteria of International Classification of Diseases (ICD-10). Out of total 80 patients, 41 were males and 39 were females, whose husbands were working abroad. 30 cases were of depression,out of which 16 were males and 14 were females.18 cases were having anxiety disorders out of which 5 were males and 13 were females. 12 cases were suffering from psychotic disorders out of which 10 were males and 2 were females.7 cases were having dissociative disorders with 1 male and 6 females.4 cases were having somatoform disorders with 2 males and 2 females.1 male and 1 female were suffering from mania.1 male and 1 female were suffering from bipolar affective disorder. 2 males were alcohol dependent and 2 males were having obsessive compulsive disorder. 1 male was having organic psychosis. Journal of College of Medical Sciences-Nepal,2011,Vol-6,No-4, 1-6 DOI: http://dx.doi.org/10.3126/jcmsn.v6i4.6718